Pengaruh Produk Domestik Bruto, Suku Bunga, dan Inflasi terhadap Foreign Direct Investment di Indonesia Periode 2000-2017 - Cindy Augare Malouni Saragih; Haryadi Haryadi; Emilia Emilia (WIDA Publishing, 2021)
The study aims to determine and analyze the influence and development of gross domestic product (GDP), interest rates, and inflation on Indonesia's foreign direct investment (FDI). The study used multiple linear regression. The secondary data used in the form of time series from 2000 to 2017 were obtained from the official websites of Bank Indonesia, Statistics Indonesia, and Investment Coordinating Board. The results of this study indicate that all variables simultaneously affect FDI in Indonesia. Partially, GDP and interest rates positively affect FDI in Indonesia, while inflation does not affect FDI in Indonesia